Kinetics Studies of Ciprofloxacin Waste Degradation Using TiO2 Nanotubes from The Anodization Process - Kustiningsih, Indar; Putri, Berliana Tristati; Putri, Martina Reza; Kurniawan, Teguh; Sari, Denni Kartika; Adiwibowo, Muhammad Triyogo; Slamet, Slamet (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
ecosystems and alter the genetic code of normal bacteria, resulting in bacterial resistance. Ciprofloxacin (CIP) is one of the antibiotics that can be an environmental challenge if it accumulates in certain quantities. The process that can be used to eliminate CIP waste from water is the photocatalysis process. This work aimed to study the kinetics of CIP degradation using TiO2 nanotubes (TNTAs) from the anodization process. TNTAs with varying water contents and voltages are produced during the anodization process. TNTAs are synthesized by anodizing organic electrolyte solutions with different voltages (40, 50, and 60 V) and water contents (20, 25, and 30%). The TNTAs are then employed in CIP waste degradation with variations in the initial pH of the waste (pH 5-8) for 3 hours. SEM and XRD were used in this investigation to characterize the catalyst. SEM results illustrate the effect of voltage and water content on the anodization process with increasing contact surface area. XRD data demonstrate the presence of anatase phase crystals produced in TNTAs. The results showed that the kinetics of the CIP degradation reaction followed order one, with the best kinetic constant attained at 8.24 hours-1.